Barriers and Supports to Substance Abuse Service Use Among Homeless Adults. Issue 2 (10th October 2013) - Brubaker, Michael D.; Amatea, Ellen A.; Torres‐Rivera, Edil; Miller, M. David; Nabors, Laura
<x xml:space="preserve">Abstract</x> Although there is a great need for substance abuse services among the homeless, many homeless individuals do not use those services. This study examined barriers and supports related to service use. Participants recognized a need for treatment and significant barriers to accessing care.